Building excellence in higher education : Singapore's experience - Meyer, Arnoud de; Ang, Jovina, 1965- (New York : Routledge, 2021)
'Over the last 30 years, Singapore has developed a system of higher education that is the envy of many other countries or regions. How has Singapore developed such a highly performing education system? Was it planned? Was it mere luck? Written by Arnoud de Meyer, who is widely regarded as one of the pre-eminent management educators and leaders in higher education, the book focuses on Singapore as an in-depth case study of how to build a system of higher education, specifically a portfolio of highly differentiated and diversified system of universities. He worked closely together with Jovina Ang during the preparation of the manuscript. This book is unique because it showcases several case studies of the emerging system of higher education, and it was written based on the insights that were drawn from the interviews with the key decision makers and actors in the system for the past 20 years including ministers and permanent secretaries of the Ministry of Education, and presidents and chairmen of the six universities. The success of this system can be attributed to several reasons: clarity of purpose of the decision makers - with clear targets in cohort participation rate, commitment to significant funding for education and research, discipline of an intelligent and well implemented governance system, flexibility in adjusting plans, and rapid and adaptive learning from the overseas partners. In the last few chapters, the authors look at the future of the system and postulate how it should be adjusted to the changes in Singapore and the world. This unique book on educational strategy would be of particular interest to educational specialists and policy makers in emerging countries who want to build a system of higher education, policy makers in mature industrialised countries who are faced with the challenge of revamping their system of higher education, strategists who are interested in dynamic capability building and philanthropists who want to use education as an equaliser of social status'--
Introduction -- Part 1. The Evolution of the Universities in Singapore. The development of Singapore's universities until 1990 -- Building universities for a knowledge economy -- Part 2. The Main Drivers of Success. Fit for purpose -- Ample research funding for universities -- Governance - The autonomous university and its impact on diversity -- Active and adaptive learning from partners -- Flexibility and quality in implementation -- Part 3. The Future. The changing context and how universities can respond -- The challenge of continuing education -- From R&D to innovation.
Includes bibliographical references and index.
Keywords: Education, Higher -- Singapore; Universities and colleges -- Singapore -- History